Dietary fiber as an alternative to pharmacological chelators for children exposed to low doses of lead - Hnida, Natalia I.; Гніда, Наталя Ігорівна; Hnidoi, Ihor M.; Гнiдой, Iгор Михайлович (Odessa : IHU, Ukraine, 2023)
The 80 random children aged 4 to 15 years were examined. About a quarter of the children had blood lead concentration (BLC) more than 5μg/dL. They also had a higher content of eosinophil cells, an increase of alanine aminotransferase activity in the blood compared to children with lower BLCs. Dietary fiber from cereals of 10 g per day was used for 30 days, as an addition to main dishes and salads during lunch for these children. As a result, the BLC, the number of eosinophils in blood and the activity of alanine aminotransferase significantly decreased.

Обстежено 80 дітей випадкової вибірки віком від 4 до 15 років. Близько чверті обстежених дітей мали концентрацію свинцю в крові (BLC) понад 5 мкг/дл. У них був виявлений більш високий, порівняно з дітьми з нижчими BLC, вміст еозинофілів крові, збільшення активності аланінамінотрансферази. Цим дітям застосовувались харчові волокна із злаків по 10 г на добу протягом 30 днів, як добавка до других страв і салатів під час обіду. У результаті достовірно знизилась BLC, зменшилась кількість еозинофілів крові й активність аланінамінотрансферази.
Hnida N. I. Dietary fiber as an alternative to pharmacological chelators for children exposed to low doses of lead / N. I. Hnida, I. M. Hnidoi // Proceedings of the Conference "Modern Problems of Pharmacology, Cosmetology and Aromology", September 22, 2023 at the Faculty of Dentistry and Pharmacy. – Odessa : IHU, Ukraine. – P. 29-33.
Keywords: environment; public health; lead exposure; children; dietary fiber; навколишнє середовище; громадське здоров'я; вплив свинцю на дітей; харчові волокна; Research Subject Categories::MEDICINE; Research Subject Categories::PHARMACY